A Randomized, Placebo-controlled, Clinical Trial of Prazosin for the Treatment of Alcohol Use Disorder. Issue 5 (September 2018) - Wilcox, Claire E.; Tonigan, J. Scott; Bogenschutz, Michael P.; Clifford, Joshua; Bigelow, Rose; Simpson, Tracy
Abstract : Objectives: The noradrenergic system plays an important role in the pathophysiology of alcohol use disorder (AUD). Medications in this class may reduce drinking. Our aims were to investigate this in a unique sample of individuals with AUD. Methods: Thirty-six individuals with AUD were randomized to treatment with prazosin, an alpha-1 noradrenergic antagonist, or placebo, for 6 weeks (target daily dose 16 mg). Hierarchical linear modeling was used to examine the effect of treatment group on rate of change in primary (drinks per week [DPW]) and several secondary outcome measures. Results: Prazosin did not significantly affect rate of reduction in alcohol use in the intent to treat sample (n = 36) compared with placebo, but did significantly increase the rate of reduction in DPW in an optimal treatment exposure subgroup (beta = −0.3; P  = 0.01; event rate ratio 0.74; confidence interval 0.59, 0.93; n = 27). Poor adherence and tolerability may have contributed to null effects. Diastolic blood pressure (DBP) moderated the effects of treatment group on rate of reduction in drinks per drinking day, supporting previous work in doxazosin, another alpha-1 antagonist. Specifically, prazosin was associated with greater rates of reduction in drinking compared with placebo in individuals with high but not low DBP. Conclusions: Our findings do not support the clinical utility of prazosin for all treatment-seeking AUD, but post hoc analyses indicate that it might have some efficacy in individuals who can tolerate it. Further work exploring the clinical utility of DBP as a treatment matching variable, and defining optimal values using sensitivity and specificity analyses, is warranted. Abstract : Supplemental Digital Content is available in the text